Impulsividade, personalidade e funções executivas em pacientes com epilepsia mioclônica juvenil - Gama, Andre Peres [UNIFESP] (2020)
According to Janz and Christian (1957) patients with juvenile myoclonic epilepsy (JME) present unsteadiness, lack of discipline, hedonism and indifference towards their disease. The objective of this study is to evaluate if there are differences in their impulsiveness and executive function, when compared to controls, besides the relation between impulsiveness and personality traits. Inclusion criteria were: JME diagnosis; age > 18 yrs; schooling > 11 yrs. And Intelligence Quotient (IQ > 70). Impulsiveness was measured by Barratt Impulsiveness Scale (BIS-11) and personality traits by the Neo Revised Personality Inventory (NEO PI-R). Neuropsychological tests used were: Vocabulary and Block Design for estimated IQ, Controlled Oral Word Association (COWA), Digit Span, Trail Making Tests (TMT) A and B, Stroop Test (ST) and Wisconsin Card Sorting Test (WSCT). A healthy control group was used for obtaining z-scores. 50 patients (35 women) with mean age 32.5 yrs. (+9.2) were evaluated. Patients showed higher scores of Total Impulsiveness (z=0.37; p=0.005) and Motor Impulsiveness (z=0.79; p<0.001) on BIS-11. Motor Impulsiveness was also associated with a higher rate of mild psychiatric disorders (p=0.035) and worse myoclonic seizure control (p=0.007). NEO PI-R results were within the normative range, however when compared to controls differences could be observed on Neuroticism (z=-0.60; p<0.001), Openness (z=0.38; p=0.043), Agreeableness (z=-0.38; p=0.033) and Conscientiousness (z=-0.53; p=0.003), with patients’ scores tending towards dysfunctionality. Correlation between BIS-11 and Neuroticism were positive for Total (r=0.395; p=0.005), Motor (r=0.375; p=0.008) and Non-Planning Impulsiveness (r=0.339; p=0.017). Conscientiousness showed negative correlation with Total (r=-0.572; p<0.001), Motor (r=-0.389; p=0.006), Attentive (r=-0.456; p=0.001) and Non-Planning Impulsiveness (r=-0.476; p=0.001). Patient’s neuropsychological results, when compared to controls, showed worse performance on COWA (z=-0.43; p=0.009) and WCST in Total Number of Completed Categories (z=-2.08; p=0.005), Trials Taken to Complete First Category (z=1.56; p=0.013), Percentage of Total Errors (z=1.56; p<0.001), Perseveration Errors (z=0.73; p=0.002), Non-Perseveration Errors (z=1.05; p=0.003) and Conceptual Level Responses (z=-1.52; p<0.001). Correlation between BIS-11 and neuropsychological tests showed that Non-Planning Impulsiveness had influence on performance, correlating with ST I (r=0.371; p=0.008), II (r=0.368; p=0.009), III (r=0.359; p=0.010), TMT A (r=0.297; p=0.036) and B (r=0.295; p=0.038). In conclusion, patients with JME seems to present Impulsiveness, executive dysfunction and personality traits that tend to dysfunctionality, leading to lack of commitment in their treatment, consequently affecting other aspects of life. Our data showed that executive functions, personality and impulsiveness are closely linked and it is possible to infer that JME presents predominantly frontal involvement, emphasizing the importance of neuropsychological rehabilitation programs.